The Effect of Number of Vehicles on Damage to Flexible Pavement Roads on Jalan Letjend Raden Suprapto, Batam City - Muhamad Agus Priyanto; Yusra Aulia Sari (Journal of Civil Engineering and Planning (JCEP), 2023)
The volume of vehicle traffic or the number of vehicles is one of the factors that affect the damage or causes of road damage. Flexible pavement is generally used on roads in Indonesia, especially in urban areas with high traffic levels. With the increasing number of vehicles every year in the city of Batam, there is a possibility that the roads in Batam will experience accelerated road damage in a relatively short period of time or not in accordance with the road plan age. The purpose of this study was to determine the effect of the number of vehicles on the level of road damage on flexible pavement. This study uses an analytical method by looking for a correlation or relationship between the number of vehicles and the number of road damage levels, and the method used is nonlinear regression analysis, namely by comparing the two variables x to the variable y and to obtain the results of the relationship function between the two variables with the R2 value of the coefficient of determination. From the equation that has been obtained, the value of the coefficient x1 = 0.00241, which can be defined if the number of vehicles crossing the road is 100 vehicles/day, then the road damage caused by the number of vehicles is 0.241, while for the coefficient x2 = -0 .0016786 which can be defined if the age of the road section reaches 100 hours, the value of road damage on this section is -0.0167, and constant = 75.418